Head capsule observations in chironomid larvae and contaminant levels in a moderately contaminated small karstic stream, Jura Mountains, eastern France - Pierre Marle; Matthieu Hyvernat (PANGAEA, 2018)
Chironomid larvae are useful bioindicators to assess environmental degradation and pollution of freshwater ecosystems. Specifically, mouthparts deformities in chironomid larvae are considered as indicators of environmental stress (e.g. caused by water pollution). In this study, a total of 50 chironomid larvae from a small karstic stream were examined for cephalic/mouthpart deformities. Five years earlier, toxicological analysis were performed on stream sediment and bryophyta and revealed a significative pollution (trace metals, pesticides and as well organic contamination). The highest contaminant concentration was 59 (+/- 11.8) mg/kg for Zn in bryophyta and 960 μg/kg for fluoranthene in sediment. According SEQ-Eau (French System of Evaluating Water Quality), this pollution is sufficient to cause adverse effects on aquatic biota. Despite this contamination, no cephalic deformities were observed on both upstream (more contaminated, RVA1) and downstream stations (RVA2). Only a mechanical wear and some broken mentum have been detected on upstream station. These results may encourage reflections on the role of certain environmental variables (e.g. dissolved oxygen concentration, water temperature, dry period, substratum), microbial processes (e.g. methylation of contaminants) regarding the toxicity level, the uptake and the effects of contaminants and some physiological mechanisms (e.g. ecdysis) for their elimination.